What makes a moving and handling people guideline work? : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Public Health at Massey University, Manawatū, New Zealand - Lidegaard, Mark (Massey University, 2018)
Moving and handling of people (MHP) is a major reason for developing musculoskeletal disorders (MSD) in the healthcare sector worldwide. To reduce MSD from MHP, many national and state level guidelines targeting MHP have been developed. However, little is known about their impact on injury claims rates, how they are intended to work, if intended users are aware of and use them, which parts of the guideline are being used, and how they are implemented. Therefore, the overarching goal of this thesis was to contribute to understanding what makes a MHP guideline work. It was addressed by examining the effects of introducing the New Zealand Accident Compensation Corporation ‘Moving and Handling People: The New Zealand Guidelines’ (MHPG), using a mixed-methods approach in five sequential studies. An analysis of claims data (Study 1) showed that MHP related claims rates declined before, but increased after the introduction of the MHPG. A study of the MHPG programme theory (Study 2) showed that key actors for implementation were MHP coordinators, H&S managers, and therapists. The developers argued for implementing a multifaceted MHP programme where implementation of organisational systems should create the foundation for implementing the core components. A questionnaire analysis (Study 3) showed that a high proportion of MHP coordinators, H&S managers, and therapists were aware of the MHPG, while a high proportion of therapists used it. In contrast, fewer carers were aware of and used it. A second questionnaire analysis (Study 4) showed that more key actors were familiar with and used the core components compared to the organisational systems. A low proportion of actors experienced change after use. Case studies (Study 5) showed that organisational motivation to implement a MHP programme was initiated by MHP related staff injuries. The implementation process was gradual, changing MHP practices during multiple steps, and dependent on a dedicated person to drive implementation. This thesis shows that making a MHP guideline work requires a dedicated actor, with support from management, to facilitate implementation and organisational changes needed. However, many contextual factors affect implementation, ranging from national, e.g. legislation and policies, to individual level, e.g. individuals conducting MHP.
Appendix 2 was removed to comply with copyright, but it may be accessed via: Lidegaard, M., Olsen, K.B., and Legg, S.J. (2019, April ). How was a national moving and handling people guideline intended to work? The underlying programme theory. Evaluation and Program Planning, 73, 163–75. https://doi.org/10.1016/j.evalprogplan.2019.01.002
Keywords: Health facilities; Risk management; New Zealand; Safety measures; Industrial accidents; Prevention; Medical personnel; Health and hygiene; Musculoskeletal system; Diseases; Accident Compensation Corporation (N.Z.)